PENGARUH RETURN ON ASSET (ROA), RETURN ON EQUITY (ROE), DAN EARNING PER SHARE (EPS) TERHADAP HARGA SAHAM PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI 2017-2021 - Laras Sari; Irine Ika Wardhan (CV. Tungga Esti, 2023)
This study aims to determine the effect of Return On Assets (ROA), Return On Equity (ROE), and Earning Per Share (EPS) on the Share Prices of Manufacturing Companies in the Food and Beverage Sub Sector which are listed on the Bei for the 2017-2021 period. In this study using a quantitative method which is based on a numerical calculation scale. The results of this study indicate that there is an influence between Return On Assets on Stock Prices. There is an influence between Return on Equity on Stock Prices. There is an influence between Earning Per Share on Share Prices. Based on research conducted on manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange for the period 2017 to 2021, it can be concluded that there is a simultaneous effect of Return On Assets, Return On Equity, and Earning Per Share on Stock Prices. The R-Square value is 37.2%, this means that 37.2% of the variation in the value of the Share Price is determined by the role of the variation in the value of Return On Assets, Return On Equity, and Earning Per Share. In other words, the contribution of Return On Assets, Return On Equity, and Earning Per Share in influencing stock prices is 37.2% while the remaining 62.8% is influenced by other variables not included in this study.